2007
DOI: 10.1097/inf.0b013e318124aa44
|View full text |Cite
|
Sign up to set email alerts
|

Admission Clinical and Laboratory Factors Associated With Death in Children With Cancer During a Febrile Neutropenic Episode

Abstract: We identified early clinical and laboratory findings significantly associated with death occurring at a later stage. Routine evaluation of these variables may prove to be useful in the early identification of children with a high-risk FN episode at risk for death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
40
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 21 publications
6
40
1
6
Order By: Relevance
“…This case illustrates that, by definition, risk-prediction rules are not perfect [9,18]. Since secondary deteriorations are well-known in children with FN [24,37,38], close follow-up is essential after step-down to outpatient management.…”
Section: Discussionmentioning
confidence: 93%
“…This case illustrates that, by definition, risk-prediction rules are not perfect [9,18]. Since secondary deteriorations are well-known in children with FN [24,37,38], close follow-up is essential after step-down to outpatient management.…”
Section: Discussionmentioning
confidence: 93%
“…Documented mortality associated with paediatric febrile neutropenia is 2% [2]. The potential for early diagnosis of bacteraemia through serum biomarkers has been the subject to extensive research [3].…”
mentioning
confidence: 99%
“…Although severe neutropenia (ANC <500 cells/ mm 3 ) has been linked to poor outcomes in febrile cancer patients, 9 our study demonstrated that, in immunocompromised children with a CVC and fever, the presence or absence of severe neutropenia at presentation did not predict the likelihood of bacteremia. These results are in concordance with a report by Schwartz et al, who observed no significant difference in the incidence of bacteremia between neutropenic and non-neutropenic pediatric cancer patients with CVCs (27.6% and 29.1%, respectively).…”
mentioning
confidence: 61%